2014
DOI: 10.1620/tjem.233.113
|View full text |Cite
|
Sign up to set email alerts
|

Juzen-Taiho-To, an Herbal Medicine, Promotes the Differentiation of Transplanted Bone Marrow Cells into Microglia in the Mouse Brain Injected with Fibrillar Amyloid <i>β</i>

Abstract: Microglia are the main immunocompetent and phagocytic cells in Alzheimer's disease (AD). Bone marrowderived microglia have been demonstrated to be more effective in antigen presentation and phagocytosis than inherent microglia in AD. Thus, microglia have received much attention in the pathogenesis of AD. The herbal medicine Juzen-taiho-to (JTT) has been reported to reduce β-amyloid (Aβ) burden in the mouse brain of an AD model. In this study, we explored the effects of JTT on the migration and differentiation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…Both JTT and A. sinensis are known to stimulate innate immune cells [22,43]. In particular, it is well-recognized that JTT exhibits “LPS-like” immunological effects [44,45] as evidenced by very similar gene expression profiles of JTT and LPS [22,46]. The current study further corroborates the emerging notion that humans may be benefiting from plant-associated bacteria through the practice of herbal medicine.…”
Section: Discussionsupporting
confidence: 82%
“…Both JTT and A. sinensis are known to stimulate innate immune cells [22,43]. In particular, it is well-recognized that JTT exhibits “LPS-like” immunological effects [44,45] as evidenced by very similar gene expression profiles of JTT and LPS [22,46]. The current study further corroborates the emerging notion that humans may be benefiting from plant-associated bacteria through the practice of herbal medicine.…”
Section: Discussionsupporting
confidence: 82%
“…Previous papers have reported that SJ possesses various biological properties, including anti-inflammatory properties, anti-cancer activity, gastroprotective effects and immune cell activation 8 9 10 11 . Recent studies using the AD animal model have suggested that the neuroprotective effects of SJ are due to reduced Aβ aggregation and reduced activation of microglia 12 13 . However, the effects of SJ on hippocampal neurogenesis and cognitive functioning have not been studied.…”
mentioning
confidence: 99%
“…First, JTT has been known for “LPS-like” immunostimulatory activity; 20,21 both JTT and LPS induce similar gene expression profiles in monocytes. 22,23 Second, many of the component herbs of JTT are roots (Table S1), which directly interact with a wide variety of soil bacteria.…”
mentioning
confidence: 99%